Developing Modified Graphene Oxide Based Sensor for Lead Ions Detection in Water. Issue 8 (17th June 2016) - Wang , Xiaozhou; Jia , Baoping; Zhang , Wei; Lin, Bencai; Wang , Qiuze; Ding, Jianning
Abstract: Blade coating method was employed to fabricate the pure graphene oxide sensors, whose sensitivity turned out to be about 10 −9 M for detection of lead ions (Pb 2+ ). To improve its ability to detect Pb 2+ at much lower concentration, modification with 50–200 nm Au nanoparticles (AuNPs) was performed on graphene oxide based on the fact that Pb 2+ could accelerate the leaching rate of AuNPs on the surface of graphene by S2 O3 2− and 2‐mercaptoethanel (2‐ME), leading to the sensitivity improved over 2 order magnitude, as well as excellent selectivity toward lead ions over a wide range of other metal ions. The approach and findings presented in this paper could also be extended to the fabrication of other heavy metal ions sensors and the improvement of their performances. Abstract : Blade coating method was employed to fabricate the graphene oxide (GO)/Au nanoparticles (AuNPs) composite sensors for detection of lead ions (Pb 2+ ) in water. Detection sensitivity of 10 −11 M was achieved, as well as excellent selectivity toward lead ions over a wide range of other metal ions.